ASSESSMENT OF HEAVY METAL ACCUMULATION IN THE STRAITS OF JOHOR: A COMPREHENSIVE STUDY ON WATER, SEDIMENT, AND AQUATIC ORGANISMS (Jurnal Teknologi (Sciences & Engineering), 2024)
The purpose of this study was to evaluate the Johor Straits' marine water quality in the vicinity of Kampung Pasir Putih. Aquatic life and aquaculture operations are at risk due to the negative consequences of land use changes and increased discharge of household, agricultural, and industrial waste, as the investigation found. The distribution and concentration levels of heavy metals (Zn, Cu, Cd, and Pb) in crabs, mussels, and sediment samples were particularly investigated in this study. For Zn, Cu, Cd, and Pb, the corresponding mean concentration values in the entire body of the crabs and mussels were 60.4 to 256.5 mg/g, 21.8 to 50.3 mg/g, 1.6 to 4.5 mg/g, and 8.2 to 23.7 mg/g dry weight. Zn and Cu continuously had greater concentrations than the other elements, although the distribution patterns of these metals differed between sampling stations. The average amounts of heavy metals in the sediment samples ranged from 17.7 to 147.1 mg/g, 17.7 to 155 mg/g, 2.4 to 5.3 mg/g, and 9.8 to 14.5 mg/g dry weight for zinc, copper, lead, and mercury, in that order. The study showed that when development increases, water quality decreases and marine organisms accumulate more heavy metals. The range of dissolved oxygen (DO) concentrations, varying from 1.36 to 6.71 mg/L, exhibited a correlation with the accumulation of heavy metals.